Cambodia : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
The Selected Issues paper discusses Cambodia's poverty and growth, private sector development, public financial management reform, and debt sustainability. It summarizes the Poverty Assessment and describes the regime of tax incentives, costs, and limits for private investment. It also summarizes the assessment of Cambodia's Public Expenditure Management system and Public Financial Management Reform Program. It highlights the key reform priorities, and provides historical background on Cambodia's external and domestic debt. It also includes a statistical appendix and a summary of the tax system.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet